1994
DOI: 10.1080/03079459408418980
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the survival of Mycoplasma gallisepticum, Mycoplasma synoviae and Mycoplasma iowae on materials found in the poultry house environment

Abstract: SUMMARYFollowing preliminary experiments to determine suitable methods for studying mycoplasma survival, suspensions of Mycoplasma gallisepticum (four strains), Mycoplasma synoviae (two strains) or Mycoplasma iowae (two strains) were seeded onto replicate samples of cotton, rubber, straw, shavings, timber, food, feathers and human hair. The organisms were also seeded onto human skin, ear and nasal mucosa. All samples were cultured for viability after 4, 8, 12 and 24 h, and then daily up to 6 days. The identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 10 publications
1
42
0
3
Order By: Relevance
“…Cultivable M. synoviae could be detected in the isolator after elimination of infected chickens, up to 3 days according to culture, in accord with the results of Christensen et al [3] and viable cells were found up to 4-5 days as suggested by mRT-PCR.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cultivable M. synoviae could be detected in the isolator after elimination of infected chickens, up to 3 days according to culture, in accord with the results of Christensen et al [3] and viable cells were found up to 4-5 days as suggested by mRT-PCR.…”
Section: Discussionsupporting
confidence: 77%
“…Such indirect transmission is rather unexpected for wall-less bacteria, which are supposed to be sensitive to osmotic shock, heating or chemical treatments. However, M. synoviae may persist on feathers up to 2 or 3 days at room temperature [3] and its high dissemination capacity has been demonstrated [16].…”
Section: Marois Et Almentioning
confidence: 99%
“…One remaining question with respect to persistence of M. gallisepticu m or other pathogenic mycoplasmas in empty buildings is the viability of mollicutes under various conditions. According to Christensen et al (1994), M. gallisepticum survived 1 to 2 days on cotton and rubber, 2 to 3 days on hair, and 2 to 4 days on feathers. Shimizu et al (1990) showed that M. gallisepticum survived 7 days in well water with horse serum, 1 to 3 days in 50% soil extract, 61 days under dry conditions at 4°C and 10 to 14 days under dry conditions at 20°C, but culture results indicated that M. gallisepticu m strain 41-91 can survive 2 to 3 days in soil and drinking water (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Horizontal transmission usually occurs by direct contact between infected and susceptible birds. However, indirect transmission via humans or fomites may play an important role because of possible persistence of M. gallisepticu m in the environment (Christensen et al, 1994). Indeed, in a recent study, we showed by culture and polymerase chain reaction (PCR) that Mycoplasma synoviae, another avian pathogen, has a high capacity for dissemination in the environment of infected poultry (Marois et al, 2000), suggesting that indirect transmission of M. synoviae or other mycoplasmas may be more important than previously considered.…”
Section: Introductionmentioning
confidence: 94%
“…Hastalık her yaş grubundaki kanatlıları etkilemesine rağmen, özellikle genç hayvanlar hastalığa karşı çok daha duyarlıdır (6,10). Hastalığın oluşumunda oral (5), horizontal (4,7), vertikal (1,19), aerosol ve konjuktival yolla (5,12) bulaşmanın etkili olduğu bildirilmektedir.…”
Section: Introductionunclassified